Nonlinear Adaptive Backstepping with ESO for the Quadrotor Trajectory Tracking Control in the Multiple Disturbances - Liu, Jie; Gai, Wendong; Zhang, Jing; Li, Yuxia (International journal of control, automation, and systems, 2019)
In this paper, we present a nonlinear adaptive backstepping with extended state observer (ESO) trajectory tracking controller for a quadrotor unmanned aerial vehicle (UAV) subject to the multiple disturbances, which include the parametric uncertainties, actuator faults and external disturbance. First, a six-degrees of freedom quadrotor UAV model with the multiple disturbances function is built. Second, the adaptive backstepping controller is designed to track the desired trajectory command aim at internal disturbance. And the adaptive backstepping controller with ESO is designed to track the desired trajectory command aim at external disturbance. Third, the stability of the system is proved by the circle criterion. Finally, under different flight scenarios, simulation results are given to demonstrate the effectiveness of the proposed method.